Ovidiu Bozgan, Bogdan Murgescu (coord.) – „Universitatea din Bucureşti” (1864-2014), Editura Universităţii din Bucureşti, 2014, 444 p., ISBN - 978-606-16-0478-4. - STAN, Ana-Maria (Studia Universitatis Babeș-Bolyai Historia, 2015)
In recent years, and particularly after 2000, there has been a notable increase in the number of works focusing on intellectual or cultural history in the Romanian historiography, a research area notoriously misused or neglected during the communist years. The book that we are discussing here is no exception to this general trend. In fact, this volume, Universitatea din Bucureşti (1864-2014), illustrates, as one of the recent examples, the renewed interest in the narrow subfield of university history. Many of the leading Romanian universities or other higher educational institutions have recently celebrated various anniversaries and, due to this festive context, a good number of studies started to analyze their institutional history and their social significance. The public was thus presented in 2010 with a comprehensive research dedicated to the 150 years of evolution of the University of Iaşi: Gheorghe Iacob, Alexandru Florin Platon (coord.) – Istoria Universităţii din Iaşi, 2010-2011, 2 tomes. It was followed, in 2012, by a detailed account of the long and varied existence of the Cluj University, a tribute to the 90 years of academic teaching in Romanian language and to the 125 years since the foundation of a modern university in Transylvania: Ovidiu Ghitta (coord.) – Istoria Universităţii Babeş-Bolyai, 2012.